2017
DOI: 10.1093/mnras/stx1378
|View full text |Cite
|
Sign up to set email alerts
|

SONS: The JCMT legacy survey of debris discs in the submillimetre

Abstract: Debris discs are evidence of the ongoing destructive collisions between planetesimals, and their presence around stars also suggests that planets exist in these systems. In this paper, we present submillimetre images of the thermal emission from debris discs that formed the SCUBA-2 Observations of Nearby Stars (SONS) survey, one of seven legacy surveys undertaken on the James Clerk Maxwell telescope between 2012 and 2015. The overall results of the survey are presented in the form of 850 µm (and 450 µm, where … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
111
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 130 publications
(119 citation statements)
references
References 244 publications
(368 reference statements)
8
111
0
Order By: Relevance
“…The North-West extension of the source HR8977 in Fig. 1 is also present in the SCUBA2 image at 850µm and ascribed to a background galaxy [10].…”
Section: Nikaobservations Of Three Stars With Known Debris Disksmentioning
confidence: 70%
See 3 more Smart Citations
“…The North-West extension of the source HR8977 in Fig. 1 is also present in the SCUBA2 image at 850µm and ascribed to a background galaxy [10].…”
Section: Nikaobservations Of Three Stars With Known Debris Disksmentioning
confidence: 70%
“…The three stars HD107146, Vega and HR8799 were selected because their disks offered the largest flux densities at 2mm predicted in extrapolating from the SCUBA2 data in [10]. Observations of these three stars were conducted on October 29 and 30 2017 at the IRAM 30m radiotelescope at Pico de Veleta in Spain in fair weather conditions (τ 225GHz = 0.2 − 0.30) using the new NIKA2 camera with its three arrays paved with Kinetic Inductance Detectors (KIDs) enclosed in a cryogenic system [11][12][13].…”
Section: Nikaobservations Of Three Stars With Known Debris Disksmentioning
confidence: 99%
See 2 more Smart Citations
“…About a hundred debris disks have been spatially resolved to date, mostly in thermal emission at 70-160μm with the Herschel Space Observatory (e.g., Booth et al 2013;Eiroa et al 2013;Matthews et al 2014;Morales et al 2016;Vican et al 2016) or at submillimeter/millimeter wavelengths with JCMT (Holland et al 2017) and ALMA (e.g., MacGregor et al 2013, 2016aSu et al 2017). Using the measured radii of a sample of Herschel-resolved disks, Pawellek et al (2014) interestingly showed that the typical grain size in these disks does not directly scale with the radiative pressure blowout particle size, but decreases with stellar luminosity.…”
Section: Introductionmentioning
confidence: 99%